Liberalization, corporate governance and the performance of privatized firms in developing countries - Boubakri, Narjess; Cosset, Jean-Claude; Guedhami, Omrane (Journal of Corporate Finance, 2005)
This paper seeks to provide an answer to the following question: when and how does privatization work? Using a sample of 230 firms headquartered in 32 developing countries, we document a significant increase in profitability, efficiency, investment and output. Our analysis shows that the changes in performance vary with the extent of macro-economic reforms and environment, and the effectiveness of corporate governance. In particular, economic growth is associated with higher profitability and efficiency gains, trade liberalization is associated with higher levels of investment and output, while financial liberalization is associated with higher output changes. Further, control relinquishment by the government is a key determinant of profitability, efficiency gains and output increases. Finally, we find higher improvements in efficiency for firms in countries in which stock markets are more developed and where property rights are better protected and enforced. These results for a sample of developing countries differ from those reported in a contemporaneous study by D'Souza et al. [D'Souza, J., Megginson, W.L., Nash, R.C., 2001. Why do privatized firms improve performance? Evidence from developed countries. Unpublished working paper. University of Oklahoma] which focuses on developed countries. These diverging findings suggest that privatization in developing countries indeed obeys to particular constraints and has a dynamic of its own.